1995
DOI: 10.1161/01.cir.92.1.24
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol Attenuates Acetylcholine-Induced Coronary Arterial Constriction in Women but Not Men With Coronary Heart Disease

Abstract: 17 beta-Estradiol modulates acetylcholine-induced coronary artery responses of female but not male atherosclerotic coronary arteries in vivo. These human data confirm reports from studies in cynomolgus monkeys that estrogen modulates the responses of atherosclerotic coronary arteries. An enhancement of endothelium-dependent relaxation by natural estrogen (as used in most hormone replacement therapy) may be important in postmenopausal women with established coronary heart disease and may contribute to the acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
176
1
8

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 483 publications
(197 citation statements)
references
References 41 publications
12
176
1
8
Order By: Relevance
“…The estrogen receptor ␤-deficient mice develop sustained systolic and diastolic hypertension, but only as they age (Ͼ6 months) (22). Estrogen reverses acetylcholineinduced vasoconstriction of coronary vessels, possibly via facilitation of endothelium-dependent relaxation (23), which may be mediated by an enhancement of NO production via stimulation of NO synthase (24). There is also a rapid nongenomic effect on endothelial cells leading to vasodilatation when estrogens are applied transdermally (25).…”
Section: Discussionmentioning
confidence: 99%
“…The estrogen receptor ␤-deficient mice develop sustained systolic and diastolic hypertension, but only as they age (Ͼ6 months) (22). Estrogen reverses acetylcholineinduced vasoconstriction of coronary vessels, possibly via facilitation of endothelium-dependent relaxation (23), which may be mediated by an enhancement of NO production via stimulation of NO synthase (24). There is also a rapid nongenomic effect on endothelial cells leading to vasodilatation when estrogens are applied transdermally (25).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have documented that E2 can induce relaxation of coronary arteries, reverse acetylcholine-induced vasoconstriction and improve exercise-induced myocardial ischemia in women with coronary artery disease (29)(30)(31)(32). Collins et al (33) showed that E2 decreases acetylcholine-induced coronary artery responses only in women, but not in men. These vasodilatory effects of estrogen are largely believed to be mediated by increased synthesis and release of nitric oxide, a potent relaxant of vascular smooth muscle (34).…”
Section: Estrogen and Vascular Tonementioning
confidence: 99%
“…8 There may be a direct effect on the vessel wall where steroid receptors are known to exist, 9 and testosterone infused into coronary arteries in men with coronary artery disease causes vasodilatation. 10 Infusion of oestradiol does not seem to cause relaxation of male coronary arteries, 11 so fall in oestradiol levels is unlikely to be responsible for the effects on arterial compliance we observed. There may be interaction through insulin pathways as testosterone replacement in middleaged obese men improves insulin sensitivity.…”
Section: Discussionmentioning
confidence: 72%